Temporary Implant Irradiation: Survey of Turkish Society of Radiation Oncology Breast Cancer Study Group - Nuri Kaydıhan; Gül Alço; Mustafa Şükrü Şenocak; Nuran Beşe (European Journal of Breast Health, 2021)

(untitled)
Objective:To understand the clinical approach of radiation oncologists during the treatment of patients with breast reconstruction.Materials and Methods:A questionnaire survey was emailed to 105 active members of the Turkish Radiation Oncology Society, the Breast Cancer Study Group. The factors associated with radiation oncologists and their current practice was identified.Results:Fifty radiation oncologists (47.6%) responded, and most of the responders (83%) were physicians who treated >50 new breast cancer patients annually. The majority of the physicians worked in academic hospitals and had more than 15 years of work experience. The early reconstruction rate was noted to be low among patients with mastectomy (<10% of the mastectomy patients) (p<0.05). Early implant irradiation with temporary tissue expander was noted to be a more common procedure. The majority of the respondents (68%) preferred to irradiate an inflated implant (20% total, 80% partial). In addition, 22% of the physicians declared that they routinely used bolus and that 60% of them used it only for patients at a high risk of local recurrence factors.Conclusion:It can thus be concluded that variations exist between experienced radiation oncologists and others. Hypofractionation is not yet commonly practiced for patients with reconstruction in Turkey. A concrete consensus can be helpful to create a homogeneity in treatment decisions and practical applications.